DETERMINATION OF THE QUALITY AND QUANTITY COMPOSITION OF FLAVONOIDS IN THE LEAVES OF GRAPE (Vitis vinifera) VARIETY PINOT NOIR (Scientific journal of the Fergana State University, 2023)
The article presents the results of the analysis of the quality and quantity composition of flavonoids in the fraction obtained using ethyl acetate, the separation of the grape leaf extract by column chromatography. HPLC brand "Agilent-1200" Column Agilent Eclipse XDB-C18 5 µm, 4.6x150 mm. The elution was carried out in isocratic mode, a mixture of 0.1% trifluoroacetic acid and acetonitrile in the ratio 70:30  was used as the mobile phase. The presence of the following flavonoids rutin, apigenin, quercetin, luteolin  was established.